Modified regeneration method of inactivated SCR denitration catalyst

By combining alkali washing and pretreatment liquid impregnation processes, the specific surface area and low-temperature denitrification efficiency of the denitrition catalyst are improved, and the lack of activity of the catalyst in low-temperature and sulfur-containing flue gas environments is solved, which significantly reduces the conversion rate of high-temperature SO2/SO3 , suitable for full load denitrification in power plants under deep peak condition.

CN119318998APending Publication Date: 2025-01-17CHINA ENERGY INVESTMENT CORP LTD +1

Patent Information

Application Number
CN202310866217.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing denitrification catalysts are insufficient in low temperature and sulfur-containing flue gas environments, resulting in low denitrification efficiency and high conversion of high temperature SO2/SO3, and the regeneration technology cannot adapt to the full load denitrification requirements in power plants under deep peak-shaving state.

Method used

The alkali washing process is used to couple the immersion and calcination process of the pretreatment liquid. Through simple water sealing and vacuum impregnation process of wide temperature activation liquid, the specific surface area and low-temperature denitrification efficiency of the catalyst are improved, and are suitable for sulfur-containing flue gas environments. And reduce the conversion rate of high temperature SO2/SO3.

Benefits of technology

The low-temperature denitrification efficiency of the inactivated SCR denitrification catalyst is improved and the high-temperature SO2/SO3 conversion rate is significantly reduced. It does not require freezing or organic blockage treatment. It has a simple process and is suitable for sulfur-containing flue gas environment in power plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004339351140000161
    Figure BDA0004339351140000161
Patent Text Reader

Abstract

The invention relates to the technical field of regeneration of deactivated catalysts, in particular to a modification regeneration method of a deactivated SCR (selective catalytic reduction) denitration catalyst, which comprises the following steps: carrying out ash removal treatment on the deactivated SCR denitration catalyst to be treated, and then carrying out chemical cleaning; immersing the cleaned catalyst into the pretreatment liquid for immersion treatment, and then drying and roasting for the first time; immersing the catalyst subjected to primary roasting into deionized water for impregnation, pre-drying, and then immersing into a wide-temperature modified active replenishing liquid for vacuum impregnation treatment; and drying the catalyst subjected to vacuum impregnation, and roasting for the second time to obtain the modified regenerated catalyst. According to the method, the low-temperature denitration efficiency of the inactivated SCR denitration catalyst can be greatly improved while the technical process is simple, the regenerated catalyst can be suitable for the sulfur-containing flue gas environment of a power plant, and the high-temperature SO2 / SO3 conversion rate can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of regeneration of deactivated catalysts, and in particular to a modification and regeneration method of a deactivated SCR denitration catalyst. Background Art

[0002] Due to the overcapacity of the power industry and the participation of thermal power in the deep peak load regulation of the power grid, more than 60% of the coal-fired units in China are currently in low-load operation, with an average annual operating hours of only 4,000 hours, resulting in the flue gas temperature entering the denitrification system often being lower than 300°C. With the continuous deepening of environmental protection policies, full-process and full-load denitrification has been put on the agenda.

[0003] The catalyst activity temperature window used in traditional power plants is between 300 and 420°C, and the catalyst flue gas temperature is generally designed to be between 320 and 430°C. When the temperature is lower than the optimal ammonia injection temperature, due to the insufficient low-temperature activity of the denitrification catalyst, in order to meet the emission regulations, power plants generally increase the amount of ammonia injection to varying degrees to improve the denitrification efficiency, which results in increased operating costs, excessive ammonia escape, shortened catalyst life, and frequent blockage of the air preheater. In addition, the air preheater is blocked by ammonium sulfate deposition, the pressure drop increases, the power of the induced draft fan increases, and the power consumption increases. In severe cases, it will cause abnormal shutdown of the power plant, bringing new problems and challenges to the safe operation of the unit. At the same time, it is also impossible to achieve full-load denitrification during the unit startup process to meet environmental protection requirements.

[0004] Faced with this situation, some power plants have adopted new wide-temperature denitration catalysts to achieve full-load denitration under deep peak load regulation, which also puts forward new requirements for denitration catalyst regeneration technology.

[0005] The current denitrification catalyst regeneration technology is either only applicable to the regeneration of conventional denitrification catalysts, and the regenerated catalyst does not have low-temperature activity; or the regenerated catalyst has good low-temperature activity but cannot adapt to the sulfur-containing flue gas environment of power plants.

[0006] The patent document with publication number CN106215980A discloses a method for regenerating a denitration catalyst, in which the denitration catalyst to be regenerated is soot-blown and cleaned, the cleaned catalyst is dried to a water content of 8-13%, and then the catalyst is frozen and impregnated with an impregnation solution containing a source of denitration active components, and the regenerated catalyst is obtained after drying and calcination. The regenerated denitration catalyst obtained by the process described in the patent has high catalytic activity and low oxidation rate, and can effectively reduce the ingredients of the active impregnation solution formula. Only the main active components need to be added, and no other co-solvents and additives are required. The formula is simple and the cost is low. However, the patented method requires freezing the dried catalyst, and has high requirements for the regeneration equipment and regeneration environment. In addition, the activation solution used in this method has a low concentration and is only suitable for conventional catalyst regeneration. The low-temperature activity of the regenerated catalyst is insufficient.

[0007] The patent document with publication number CN111715217A discloses a method for regenerating a denitration catalyst, which pre-treats the catalyst with compressed air purging, physical cleaning, and chemical cleaning. The catalyst is dried once to a water content of less than 15%, and then implanted with a tetrabutyl titanate solution once and dried twice, and a manganese salt is implanted twice. Then, it is optionally dried three times and implanted with a vanadium salt and a tungsten salt three times, and a regenerated catalyst is obtained through a roasting step and a hardening step. The method of implanting titanium can increase the compressive strength and wall thickness of the catalyst and increase the specific surface area. The method of implanting manganese can broaden the operating temperature range of the catalyst and realize wide-temperature range denitration of the regenerated catalyst. However, this method will block the original micropores of the catalyst after the titanium source is implanted, and the increase in the specific surface area of ​​the regenerated catalyst is mainly due to the introduction of the new titanium source. When the catalyst is used in a high-dust flue gas environment, the newly implanted titanium source can be easily blown off by the dust, resulting in a rapid decrease in the specific surface area of ​​the catalyst. At the same time, the low-temperature activity of the regenerated catalyst in this patent is mainly due to the introduction of manganese salts. Since the manganese catalyst in the manganese-based low-temperature catalyst will react with the sulfur in the sulfur-containing flue gas, causing the catalyst to fail quickly, this wide temperature range regeneration catalyst is not suitable for low-temperature denitrification of sulfur-containing flue gas.

[0008] In view of this, the modification and regeneration method of deactivated deNOx catalyst needs further development and research. Summary of the invention

[0009] The purpose of the present invention is to provide a modified regeneration method for a deactivated SCR denitration catalyst in view of the deficiencies in the prior art, wherein the specific surface area of ​​the catalyst is increased by coupling an alkaline washing process with an impregnation process of a pretreatment liquid and a roasting process; a modified regenerated catalyst can be obtained by a simple water seal and a vacuum impregnation process of a wide temperature range activation liquid; the catalyst regenerated by the method has a higher low-temperature denitration efficiency and a lower high-temperature SO2 / SO3 conversion rate, and the method does not require processes such as freezing and organic blockage treatment; that is, the method can greatly improve the low-temperature denitration efficiency of the deactivated SCR denitration catalyst while achieving a simple process, and the regenerated catalyst can be applied to the sulfur-containing flue gas environment of a power plant and can significantly reduce the high-temperature SO2 / SO3 conversion rate.

[0010] In order to achieve the above object, the present invention provides the following technical solutions:

[0011] A method for modifying and regenerating a deactivated SCR denitration catalyst comprises the following steps:

[0012] (1) performing ash removal treatment on the deactivated SCR denitration catalyst to be treated, and obtaining a ash-removed catalyst, the through-pore rate of which reaches 95% or more (e.g., 96%, 97%, 98%, 99%);

[0013] (2) chemically cleaning the deashed catalyst to remove toxic substances on the catalyst surface and in the micropores to obtain a cleaned catalyst; preferably, the chemical cleaning is selected from an alkaline cleaning process and / or an acid cleaning process;

[0014] (3) immersing the cleaned catalyst into a pretreatment solution for immersion treatment to obtain an impregnated catalyst;

[0015] (4) drying and calcining the impregnated catalyst to obtain a first calcined catalyst;

[0016] (5) immersing the catalyst after the primary calcination in deionized water for impregnation treatment; then pre-drying the impregnated catalyst at room temperature to a water content of 15-20 wt % (e.g., 16 wt %, 18 wt %, 19 wt %);

[0017] (6) impregnating the pre-dried catalyst of step (5) into a wide temperature range modified active replenisher solution, and performing vacuum impregnation treatment to obtain a vacuum impregnated catalyst;

[0018] (7) The vacuum impregnated catalyst obtained in step (6) is dried and calcined for a second time to obtain a modified regenerated catalyst.

[0019] Herein, there is no particular restriction on the acquisition of the deactivated SCR denitration catalyst to be treated. According to the modification and regeneration method provided by the present invention, in some embodiments, the deactivated SCR denitration catalyst to be treated is a vanadium-titanium-based SCR denitration catalyst.

[0020] In step (1), the ash removal treatment can use a soot blowing technique known in the art to remove the accumulated ash on the catalyst surface and in the pores, including but not limited to a compressed air purging process, a high-pressure water washing process, and a negative pressure dust suction process. In some embodiments, the ash removal treatment is selected from one or more of a compressed air purging process, a high-pressure water washing process, and a negative pressure dust suction process.

[0021] In some embodiments, in step (2), the chemical cleaning process is to first subject the deashed catalyst to an alkali washing process, and then subject the alkali washed catalyst to an acid washing process.

[0022] In some embodiments, the alkaline washing process is: immersing the deashed catalyst in an alkaline cleaning solution for immersion cleaning, the immersion temperature is 15-70°C (e.g., 20°C, 25°C, 30°C, 40°C, 50°C, 60°C), and the immersion time is 1-2h (e.g., 1.5h); then the immersed catalyst is ultrasonically cleaned, and the ultrasonic treatment frequency is 20-120KHz (e.g., 25KHz, 30KHz, 40KHz, 60KHz, 80KHz , 100KHz), the treatment temperature is 15-70°C (e.g., 20°C, 25°C, 30°C, 40°C, 50°C, 60°C), the treatment time is 0.5-3h (e.g., 1h, 1.5h, 2h, 2.5h), to obtain the catalyst after alkali washing; preferably, the alkaline cleaning solution is selected from sodium hydroxide aqueous solution or potassium hydroxide aqueous solution, and its concentration is 1-10wt% (e.g., 1.5wt%, 2wt%, 4wt%, 5wt%, 6wt%, 8wt%).

[0023] In some embodiments, the acid washing process is: the catalyst after alkali washing is placed in an acidic cleaning solution for cleaning, the cleaning method is bubbling cleaning, the cleaning temperature is 15-70°C (e.g., 20°C, 25°C, 30°C, 40°C, 50°C, 60°C), and the cleaning time is 0.1-2h (e.g., 0.2h, 0.4h, 0.6h, 0.8h, 1h, 1.5h); then the catalyst after acid washing is rinsed with deionized water 1-2 times to obtain a cleaned catalyst; preferably, the acidic cleaning solution is selected from an aqueous sulfuric acid solution or an aqueous ammonium sulfate solution, and its concentration is 0.1wt%-5wt% (e.g., 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt%).

[0024] In some embodiments, in step (3), the pretreatment solution includes: water, a penetrant and a pore expander; wherein:

[0025] The mass ratio of the penetrant to the pore-enlarging agent is 1:10 to 50 (e.g., 1:12, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45);

[0026] The mass ratio of the pore expanding agent to water is 1 to 5:100 (e.g., 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100).

[0027] In some embodiments, the penetrant is the environmentally friendly penetrant JFC; and the pore expander is polyethylene glycol.

[0028] In the present invention, a compound mixture of a penetrant and a pore-enlarging agent is selected as the pretreatment liquid. The purpose of compounding the penetrant and the pore-enlarging agent is to achieve an excellent pore-enlarging effect, that is, to increase and restore the amount of micropores on the catalyst surface and improve the specific surface area of ​​the regenerated catalyst, so that the active ingredients can be more evenly dispersed on the catalyst surface and in the micropores, increase the reaction area, and improve the catalyst activity.

[0029] In some embodiments, the immersion process in the pretreatment liquid includes: an immersion time of 1-4 h (e.g., 1.5 h, 2 h, 3 h, 3.5 h), and an immersion temperature of 20-70°C (e.g., 25°C, 30°C, 40°C, 50°C, 60°C).

[0030] In some embodiments, in step (4), the drying temperature is 100-120° C. (eg, 105° C., 110° C., 115° C.) and the drying time is 1-2 h (eg, 1.5 h).

[0031] In some embodiments, in step (4), the process conditions of the first calcination include: a calcination temperature of 350-500°C (eg, 360°C, 400°C, 450°C), and a calcination time of 1-3h (eg, 1.5h, 2h, 2.5h).

[0032] In some embodiments, in step (5), the immersion treatment in deionized water is performed for 1-2 h (e.g., 1.5 h) at room temperature (e.g., 20° C. or 25° C.);

[0033] In some embodiments, in step (5), the pre-drying method is air-dried at room temperature.

[0034] In some embodiments, in step (6), the process conditions of the vacuum impregnation treatment include: vacuum degree of 0.01-0.06MPa (e.g., 0.055MPa, 0.05MPa, 0.04MPa, 0.03MPa, 0.02MPa), impregnation time of 0.1-2h (e.g., 0.2h, 0.4h, 0.6h, 0.8h, 1.5h), impregnation temperature of 15-95°C (e.g., 20°C, 30°C, 40°C, 50°C, 60°C, 80°C). The use of vacuum impregnation can further improve the catalyst activity.

[0035] In some embodiments, in step (6), based on a total amount of 100 parts by weight, the wide temperature modified active supplement solution includes the following components in parts by weight:

[0036] 1-3 parts of ammonium metavanadate, such as 1.2 parts, 1.5 parts, 1.8 parts, 2.0 parts, 2.5 parts, 2.8 parts,

[0037] 0-5 parts of ammonium metatungstate, such as 0.1 parts, 0.5 parts, 1.0 parts, 2.0 parts, 3.0 parts, 4.0 parts, 4.5 parts,

[0038] 0-3 parts of cerium ammonium nitrate, such as 0.1 parts, 0.5 parts, 1.0 parts, 1.5 parts, 1.8 parts, 2.0 parts, 2.5 parts, 2.8 parts,

[0039] 0-1.5 parts of antimony acetate, such as 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts,

[0040] 0-5 parts of ammonium molybdate, such as 0.1 parts, 0.5 parts, 1.0 parts, 2.0 parts, 3.0 parts, 4.0 parts, 4.5 parts,

[0041] 1-5 parts of monoethanolamine, such as 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts,

[0042] The balance was deionized water.

[0043] In some embodiments, in step (7), the drying temperature is 100-120°C (e.g., 105°C, 110°C, 115°C), and the time is 0.5-2h (e.g., 1h, 1.5h). In some embodiments, the process conditions of the second calcination include: the calcination temperature is 350-450°C (e.g., 360°C, 400°C, 420°C), and the calcination time is 1-5h (e.g., 1.5h, 2h, 3h, 4h).

[0044] In the method of the present invention, there is no need for freezing, organic blockage treatment and other processes, and the process is simple. After the deactivated honeycomb denitrification catalyst is regenerated by the method of the present invention, the specific surface area of ​​the regenerated catalyst can be effectively increased, and the active components of the catalyst are selectively distributed on the catalyst surface and in the micropores formed on the surface, which can greatly improve the low-temperature denitrification efficiency of the deactivated SCR denitrification catalyst, and the regenerated catalyst can be applied to the sulfur-containing flue gas environment of the power plant and can significantly reduce the high-temperature sulfur conversion rate. DETAILED DESCRIPTION

[0045] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.

[0046] <Source of raw materials>

[0047] The vanadium-tungsten-titanium deactivated honeycomb denitration catalyst of a domestic coal-fired power plant after running for 24,000 hours has a denitration rate of 65.7% and a specific surface area of ​​43.02m 2 / g, SO2 / SO3 conversion rate α is 0.32.

[0048] Example 1

[0049] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0050] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0051] (2) Chemical cleaning: The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0052] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0053] (3) Pretreatment liquid impregnation: The acid-washed catalyst is impregnated in the pretreatment liquid and soaked at 50° C. for 1 h to obtain a catalyst impregnated with the pretreatment liquid;

[0054] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0055] (4) First calcination: The catalyst impregnated with the pretreatment solution is dried at 120°C for 1 hour, and then calcined at 400°C for 2 hours to obtain a first calcined catalyst;

[0056] (5) Immersing in water: The catalyst obtained after the primary calcination is placed in deionized water and soaked at 20° C. (room temperature) for 1 hour, and then pre-dried in a forced air dryer to a water content of 20 wt %;

[0057] (6) Impregnation with modified active replenisher: The pre-dried catalyst is impregnated in a wide temperature range modified active replenisher for vacuum impregnation at a vacuum degree of 0.03 MPa, a temperature of 25° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0058] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium molybdate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0059] (7) Secondary calcination: The vacuum impregnated catalyst was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0060] Example 2

[0061] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0062] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0063] (2) Chemical cleaning: The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0064] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0065] (3) Pretreatment liquid impregnation: The acid-washed catalyst is impregnated in the pretreatment liquid and soaked at 50° C. for 1 h to obtain a catalyst impregnated with the pretreatment liquid;

[0066] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0067] (4) First calcination: The catalyst impregnated with the pretreatment solution is dried at 120°C for 1 hour, and then calcined at 400°C for 2 hours to obtain a first calcined catalyst;

[0068] (5) Immersing in water: The catalyst obtained after the primary calcination is placed in deionized water and soaked at 20° C. (room temperature) for 1 hour, and then pre-dried in a forced air dryer to a water content of 20 wt %;

[0069] (6) Impregnation with modified active replenisher: The pre-dried catalyst is impregnated in a wide temperature range modified active replenisher for vacuum impregnation at a vacuum degree of 0.04 MPa, a temperature of 20° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0070] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium tungstate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0071] (7) Secondary calcination: The vacuum impregnated catalyst was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0072] Example 3

[0073] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0074] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0075] (2) Chemical cleaning: The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0076] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0077] (3) Pretreatment liquid impregnation: The acid-washed catalyst is impregnated in the pretreatment liquid and soaked at 50° C. for 1 h to obtain a catalyst impregnated with the pretreatment liquid;

[0078] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0079] (4) First calcination: The catalyst impregnated with the pretreatment solution is dried at 120°C for 1 hour, and then calcined at 400°C for 2 hours to obtain a first calcined catalyst;

[0080] (5) Immersing in water: The catalyst obtained after the primary calcination is placed in deionized water and soaked at 20° C. (room temperature) for 1 hour, and then pre-dried in a forced air dryer to a water content of 20 wt %;

[0081] (6) Impregnation with modified active replenisher: The pre-dried catalyst is impregnated in a wide temperature range modified active replenisher for vacuum impregnation at a vacuum degree of 0.02 MPa, a temperature of 20° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0082] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium cerium nitrate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0083] (7) Secondary calcination: The vacuum impregnated catalyst was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0084] Example 4

[0085] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0086] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0087] (2) Chemical cleaning: The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0088] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0089] (3) Pretreatment liquid impregnation: The acid-washed catalyst is impregnated in the pretreatment liquid and soaked at 50° C. for 1 h to obtain a catalyst impregnated with the pretreatment liquid;

[0090] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0091] (4) First calcination: The catalyst impregnated with the pretreatment solution is dried at 120°C for 1 hour, and then calcined at 400°C for 2 hours to obtain a first calcined catalyst;

[0092] (5) Immersing in water: The catalyst obtained after the primary calcination is placed in deionized water and soaked at 20° C. (room temperature) for 1 hour, and then pre-dried in a forced air dryer to a water content of 20 wt %;

[0093] (6) Impregnation with modified active replenisher: The pre-dried catalyst is impregnated in a wide temperature range modified active replenisher for vacuum impregnation at a vacuum degree of 0.03 MPa, a temperature of 20° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0094] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of antimony acetate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0095] (7) Secondary calcination: The vacuum impregnated catalyst was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0096] Example 5

[0097] The steps of the modification and regeneration method of the deactivated SCR denitration catalyst refer to Example 1, except that, in step (6), the content of ammonium metavanadate in the wide temperature modified active replenisher is 1wt%, the content of monoethanolamine is 1wt%, the immersion time is 1.5h, and the other conditions are the same as in Example 1.

[0098] Example 6

[0099] The steps of the modification and regeneration method of the deactivated SCR denitration catalyst refer to Example 1, except that, in step (6), the content of ammonium metavanadate in the wide temperature modified active replenisher is 3wt%, the content of monoethanolamine is 5wt%, the immersion time is 0.1h, and the other conditions are the same as in Example 1.

[0100] Example 7

[0101] The steps of the modified regeneration method of the deactivated SCR denitration catalyst refer to Example 1, except that in step (3), the pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of the penetrant JFC to the deionized water is 0.1:100, and the mass ratio of the polyethylene glycol to the deionized water is 1:100.

[0102] Example 8

[0103] The steps of the modified regeneration method of the deactivated SCR denitration catalyst refer to Example 1, except that in step (3), the pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of the penetrant JFC to the deionized water is 0.1:100, and the mass ratio of the polyethylene glycol to the deionized water is 5:100.

[0104] Comparative Example 1

[0105] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0106] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, a high-pressure water flushing process was used to further flush and remove the remaining ash in the catalyst pores and module gaps, and a deashed catalyst was obtained, the catalyst through-hole rate of which reached 95%;

[0107] (2) Chemical cleaning: The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0108] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and washed by bubbling at 20° C. for 1 h to obtain an acid-washed catalyst;

[0109] (3) Immerse the acid-washed catalyst in deionized water, rinse with bubbling water for 0.25 h, and repeat the rinsing twice;

[0110] (4) pre-drying the rinsed catalyst in an air dryer until the water content is 20 wt %;

[0111] (5) vacuum impregnating the pre-dried catalytic impregnant in a wide temperature modified active replenisher at a vacuum degree of 0.03 MPa, a temperature of 20° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0112] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium molybdate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0113] (6) The vacuum impregnated catalyst was dried at 120°C for 1 h and then calcined at 450°C for 3 h to obtain a modified regenerated catalyst.

[0114] Comparative Example 2

[0115] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0116] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the catalyst pores and module gaps was removed by a high-pressure water flushing process to obtain a deashed catalyst with a catalyst through-hole rate of 95%;

[0117] (2) The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0118] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0119] (3) immersing the acid-washed catalyst in a pretreatment solution and soaking it at 50° C. for 1 hour to obtain an impregnated catalyst;

[0120] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0121] (4) drying the impregnated catalyst at 120° C. for 1 h, and then calcining it for the first time at 400° C. for 2 h to obtain a catalyst after primary calcination;

[0122] (5) Immersing in water: The catalyst obtained after the primary calcination is placed in deionized water and soaked at 20° C. (room temperature) for 1 hour, and then pre-dried in a forced air dryer to a water content of 20 wt %;

[0123] (6) immersing the obtained pre-dried catalyst in a wide temperature modified active replenisher for 0.25 h at normal pressure to obtain a catalyst impregnated at normal pressure;

[0124] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium heptamolybdate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0125] (7) The catalyst obtained after atmospheric pressure impregnation was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0126] Comparative Example 3

[0127] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0128] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0129] (2) The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0130] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0131] (3) Immerse the acid-washed catalyst in deionized water, rinse with bubbling water for 0.25 h, and repeat the rinsing twice;

[0132] (4) pre-drying the rinsed catalyst in an air dryer until the water content is 20 wt %;

[0133] (5) soaking the pre-dried catalyst impregnating agent in a wide temperature modified active replenishing solution at normal pressure for 0.25 h;

[0134] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium heptamolybdate is 3wt%, the content of monoethanolamine is 3wt%, and the balance is deionized water;

[0135] (6) The catalyst after atmospheric pressure impregnation was dried at 120°C for 1 h, and then calcined at 450°C for 3 h to obtain a modified regenerated catalyst.

[0136] Comparative Example 4

[0137] The modified regeneration method of the deactivated SCR denitration catalyst comprises the following steps:

[0138] (1) Ash removal: A vanadium-tungsten-titanium honeycomb denitration catalyst that had been in operation for 24,000 hours in a domestic coal-fired power plant was used as the catalyst to be treated. The ash on the surface and pores of the catalyst to be treated was removed by a compressed air purge process. Then, the remaining ash in the pores and module gaps of the catalyst was further removed by a high-pressure water flushing process. The catalyst after ash removal was obtained, and its through-porosity reached 95%;

[0139] (2) The deashed catalyst was immersed in a 5 wt% NaOH aqueous solution at 20°C for 1 h; then placed in clean water and subjected to ultrasonic treatment at 20°C and 40 kHz for 0.5 h;

[0140] The catalyst obtained after ultrasonic treatment was immersed in a 2 wt % H2SO4 aqueous solution and cleaned by bubbling at 20° C. for 1 h, and then rinsed with deionized water 1-2 times to obtain an acid-washed catalyst;

[0141] (3) immersing the acid-washed catalyst in a pretreatment solution and soaking it at 50° C. for 1 hour to obtain an impregnated catalyst;

[0142] The pretreatment liquid is a mixture of penetrant JFC, polyethylene glycol and deionized water, wherein the mass ratio of penetrant JFC to deionized water is 0.1:100, and the mass ratio of polyethylene glycol to deionized water is 2:100;

[0143] (4) drying the impregnated catalyst at 120° C. for 1 h, and then calcining it for the first time at 400° C. for 2 h to obtain a catalyst after primary calcination;

[0144] (5) placing the obtained catalyst after the primary calcination into deionized water and soaking it at 20° C. for 1 hour, and then pre-drying it in a forced air dryer to a water content of 20 wt %;

[0145] (6) impregnating the obtained pre-dried catalyst in a wide temperature modified active replenisher for vacuum impregnation at a vacuum degree of 0.03 MPa, a temperature of 20° C., and a time of 0.25 h to obtain a vacuum impregnated catalyst;

[0146] Based on the total weight of the wide temperature modified active replenisher, the content of ammonium metavanadate is 2wt%, the content of ammonium heptamolybdate is 3wt%, the content of oxalic acid is 2wt%, and the balance is deionized water;

[0147] (7) The vacuum impregnated catalyst was dried at 120°C for 1 h, and then calcined for a second time at 450°C for 3 h to obtain a modified regenerated catalyst.

[0148] <Test Method>

[0149] (1) Catalyst denitration rate test: An experimental platform was built, and the deactivated catalyst and the regenerated catalyst prepared in each embodiment and comparative example were selected and placed in a stainless steel fixed bed reactor. The temperature was raised to 260° C. and simulated flue gas (SO2 = 500 ppm, NO x =NH3=300ppm, O2=4%, H2O=10%, N2 as balance gas), space velocity=8000h -1 The catalyst inlet and outlet NO was tested using the American Thermoelectric THERMO42i flue gas analyzer. x concentration.

[0150] The calculation formula of denitrification efficiency η is:

[0151]

[0152] Where: NO at the reactor inlet x Concentration, in ppm; NO at the reactor outlet x Concentration, in ppm.

[0153] (2) SO2 / SO3 conversion test: An experimental platform was built, and the deactivated catalyst and the regenerated catalyst prepared in each embodiment and comparative example were selected and placed in a stainless steel fixed bed reactor. The temperature was raised to 380°C, and simulated flue gas (composition includes: SO2 = 500 ppm, O2 = 3% by volume, H2O = 10% by volume, and the balance gas is N2) was introduced at a mass space velocity of 8000 h -1 , aging for more than 40 hours, using temperature-controlled condensation method to absorb SO3 at the inlet and outlet of the denitrification reactor, using ion chromatograph to analyze and determine the inlet and outlet SO3 content, taking the average value, marked as S1 and S2 respectively, and using MGA5 smoke analyzer to test the inlet SO2 concentration as S3. Calculate the SO2 / SO3 conversion rate α according to the following formula:

[0154] α=100%×(S2-S1) / S3.

[0155] (3) Catalyst BET test: Deactivated catalysts with a mesh size of 40-60 and regenerated catalyst particles prepared in various embodiments and comparative examples were selected and the BET of each catalyst was tested using an AutoChemⅡ2920 fully automatic chemisorption instrument produced by Micromeritics.

[0156] Examples 1 to 8, comparative examples 1 to 4, and the deactivated catalyst to be treated were respectively tested for denitration efficiency η, SO2 / SO3 conversion rate α, and BET test, and were marked as Test Examples 1 to 8, Test Examples 9 to 12, and Test Example 13, respectively.

[0157] The test results of each test case are shown in Table 1.

[0158] Table 1 Test results of each catalyst

[0159] <![CDATA[Specific surface area (m 2 / g)]]> η(%) α(%) Test Example 1 51.7 84.6 0.21 Test Example 2 50.9 82.7 0.20 Test Example 3 51.3 81.9 0.18 Test Example 4 50.5 84.2 0.28 Test Example 5 51.2 83.9 0.35 Test Example 6 50.6 84.0 0.19 Test Example 7 49.8 83.2 0.20 Test Example 8 52.2 85.1 0.23 Test Example 9 46.3 80.1 0.32 Test Example 10 51.0 80.5 0.27 Test Example 11 46.4 79.6 0.38 Test Example 12 49.9 76.8 0.52 Test Example 13 43.02 65.7 0.32

[0160] It can be seen from the experimental records in Table 1 that the method of the present invention does not require processes such as freezing and organic blockage treatment, and the process is simple; and the low-temperature denitrification efficiency of the regenerated catalyst obtained by the method is greatly improved. At the same time, it can be applied to the sulfur-containing flue gas environment of power plants and can significantly reduce the high-temperature sulfur conversion rate.

[0161] By comparing Comparative Example 1 with Example 1, it can be seen that after the pickling step, the pretreatment liquid impregnation treatment without the compounding of the penetrant and the pore-enlarging agent is not conducive to the formation of micropores on the catalyst surface, and the increase in specific surface area is small, which results in poor improvement in the catalyst low-temperature denitration efficiency and high-temperature sulfur conversion rate. By comparing Comparative Examples 2-3 with Example 1, it can be seen that the wide-temperature modified active supplement liquid is impregnated under normal pressure conditions, and the pretreatment liquid impregnation treatment without the compounding of the penetrant and the pore-enlarging agent and the wide-temperature modified active supplement liquid are impregnated under normal pressure conditions, which are not conducive to the improvement of catalyst activity. By comparing Comparative Example 4 with Example 1, it can be seen that the wide-temperature modified active supplement liquid does not use monoethanolamine, which is not conducive to the improvement of catalyst activity.

[0162] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.

Claims

1. A method for modifying and regenerating a deactivated SCR denitration catalyst, characterized in that: The following steps are involved: (1) performing ash removal treatment on the deactivated SCR denitration catalyst to be treated, and obtaining a ash-removed catalyst, the through-pore rate of which reaches more than 95%; (2) chemically cleaning the deashed catalyst to remove toxic substances on the catalyst surface and in the micropores to obtain a cleaned catalyst; preferably, the chemical cleaning is selected from an alkaline cleaning process and / or an acid cleaning process; (3) immersing the cleaned catalyst into a pretreatment solution for immersion treatment to obtain an impregnated catalyst; (4) drying and calcining the impregnated catalyst to obtain a first calcined catalyst; (5) immersing the catalyst after the primary calcination in deionized water for immersion treatment; The impregnated catalyst is then pre-dried at room temperature to a water content of 15-20 wt %; (6) impregnating the pre-dried catalyst of step (5) into a wide temperature range modified active replenisher solution, and performing vacuum impregnation treatment to obtain a vacuum impregnated catalyst; (7) The vacuum impregnated catalyst obtained in step (6) is dried and calcined for a second time to obtain a modified regenerated catalyst.

2. The modification and regeneration method according to claim 1, characterized in that: The deactivated SCR denitration catalyst to be treated is a vanadium-titanium based SCR denitration catalyst.

3. The modification and regeneration method according to claim 1, characterized in that: In step (1), the dust removal process is selected from one or more of a compressed air blowing process, a high-pressure water washing process and a negative pressure dust removal process.

4. The modification and regeneration method according to claim 1, characterized in that: In step (2), the chemical cleaning process is to first perform an alkali washing process on the catalyst after ash removal, and then perform an acid washing process on the catalyst after alkali washing; The alkaline washing treatment process is: immersing the deashed catalyst in an alkaline cleaning solution for immersion cleaning, the immersion temperature is 15-70°C, and the immersion time is 1-2h; then the immersed catalyst is ultrasonically cleaned, the ultrasonic treatment frequency is 20-120KHz, the treatment temperature is 15-70°C, and the treatment time is 0.5-3h, to obtain an alkaline washed catalyst; preferably, the alkaline cleaning solution is selected from a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and its concentration is 1-10wt%; The acid washing process is as follows: the catalyst after alkali washing is placed in an acidic cleaning solution for cleaning, the cleaning method is bubbling cleaning, the cleaning temperature is 15-70°C, and the cleaning time is 0.1-2h; then the catalyst after acid washing is rinsed with deionized water for 1-2 times to obtain a cleaned catalyst; preferably, the acidic cleaning solution is selected from a sulfuric acid aqueous solution or an ammonium sulfate aqueous solution, and its concentration is 0.1wt%-5wt%.

5. The modification and regeneration method according to claim 1, characterized in that: In step (3), the pretreatment liquid comprises: water, a penetrant and a pore expander; wherein the mass ratio of the penetrant to the pore expander is 1:10-50; the mass ratio of the pore expander to water is 1-5:100; the penetrant is preferably an environmentally friendly penetrant JFC; the pore expander is preferably polyethylene glycol; The immersion process in the pretreatment liquid includes: an immersion time of 1-4 hours and an immersion temperature of 20-70°C.

6. The modification and regeneration method according to claim 1, characterized in that: In step (4), the drying temperature is 100-120° C. and the drying time is 1-2 h; and / or The process conditions of the first calcination include: a calcination temperature of 350-500° C. and a calcination time of 1-3 hours.

7. The modification and regeneration method according to claim 1, characterized in that: In step (5), the immersion treatment in deionized water is carried out for 1-2 hours at room temperature; Preferably, the pre-drying method is air-dried at room temperature.

8. The modification and regeneration method according to claim 1, characterized in that: In step (6), the process conditions of the vacuum impregnation treatment include: vacuum degree of 0.01-0.06MPa, impregnation time of 0.1-2h, and impregnation temperature of 15-95°C.

9. The modification and regeneration method according to claim 1, characterized in that: In step (6), based on a total amount of 100 parts by weight, the wide temperature modified active supplement solution includes the following components in parts by weight: 1-3 parts of ammonium metavanadate, 0-5 parts of ammonium metatungstate, 0-3 parts of cerium ammonium nitrate, 0-1.5 parts of antimony acetate, 0-5 parts of ammonium molybdate, 1-5 parts of monoethanolamine, The balance was deionized water.

10. The modification and regeneration method according to claim 1, characterized in that: In step (7), the drying temperature is 100-120° C. and the drying time is 0.5-2 h; and / or The process conditions of the second calcination include: a calcination temperature of 350-450° C. and a calcination time of 1-5 hours.

Citation Information

Patent Citations

  • Regeneration method for denitration catalyst

    CN106215980A

  • Denitration catalyst regeneration method

    CN111715217A

Cited By

  • Regeneration liquid and regeneration method of corrugated plate denitration catalyst

    CN120790245A

  • Regeneration method and regeneration equipment for waste denitration catalyst

    CN122183721A